2016
DOI: 10.1073/pnas.1519772113
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of influenza variants resistant to a viral endonuclease inhibitor

Abstract: The influenza endonuclease is an essential subdomain of the viral RNA polymerase. It processes host pre-mRNAs to serve as primers for viral mRNA and is an attractive target for antiinfluenza drug discovery. Compound L-742,001 is a prototypical endonuclease inhibitor, and we found that repeated passaging of influenza virus in the presence of this drug did not lead to the development of resistant mutant strains. Reduced sensitivity to L-742,001 could only be induced by creating point mutations via a random mutag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(89 citation statements)
references
References 56 publications
3
86
0
Order By: Relevance
“…Additionally, results of a recent study by Song and colleagues suggest that other substitutions beyond PA T20A are unlikely to arise through serial passage in MDCK cells. Amino acid substitutions in the endonuclease domain of the PA protein, such as I79L, F105S, and E119D, were observed only after application of PCR mutagenesis, virus rescue, and sequential passage of rescued viruses in the presence of LL-742,001 (82). These mutations induced a 2-to 29.4-fold change in IC 50 or EC 50 s compared to wild-type virus results.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, results of a recent study by Song and colleagues suggest that other substitutions beyond PA T20A are unlikely to arise through serial passage in MDCK cells. Amino acid substitutions in the endonuclease domain of the PA protein, such as I79L, F105S, and E119D, were observed only after application of PCR mutagenesis, virus rescue, and sequential passage of rescued viruses in the presence of LL-742,001 (82). These mutations induced a 2-to 29.4-fold change in IC 50 or EC 50 s compared to wild-type virus results.…”
Section: Discussionmentioning
confidence: 98%
“…More conclusive evidence requires crystal structures obtained in the presence of an RNA substrate. As of today, only cocrystal structures with mononucleotides have been determined …”
Section: Structure and Functions Of The Influenza Virus Polymerase Comentioning
confidence: 99%
“…Two groups examined the emergence of PA endonuclease inhibitorresistant viruses during serial passages in vitro. Nakazawa et al reported the emergence of a T20A PA substitution known to increase EC 50 s 3-fold for the first-generation PA inhibitor L-742,001, but Song and coworkers were unable to identify any L-742,001 resistance by this method (46,53). Both Song and Stevaert and their respective colleagues used a mutational library or directed mutagenesis to identify potential resistance markers.…”
Section: Discussionmentioning
confidence: 99%
“…Both Song and Stevaert and their respective colleagues used a mutational library or directed mutagenesis to identify potential resistance markers. These groups identified residues within critical metal-binding motifs necessary for enzymatic activity (including H41A, G81T/F, and E119D) that increased the 50% inhibitory concentrations of L-742,001 in the minireplicon assay and the susceptibility to the drug in MDCK cells (53,54). However, additional studies are required to determine how these substitutions could affect influenza B virus fitness, taking into consideration the conserved nature of the PA endonuclease domain among influenza A and B genera (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation